Analisa Kinerja Keuangan Terhadap Financial Distress Pada Perusahaan Tekstil dan Garment Di BEI - Ardi, Muhammad Fatikh Satrio; Desmintari, Desmintari; Yetty, Fitri (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
This research is using quantitative study aimed to see the influence of liquidity, leverage, and profitability on financial distress. This research using textile and garment company that listed in Indonesian Stock Exchange as sample. The dependent variable in this study is financial distress and the independent variable in this study is liquidity that measured by current ratio, leverage that measured by debt to total asset ratio and profitability that measured by return on asset ratio. The sampling method in this study is using purposive sampling method. The sample used in this study is 17 Textile and garment company. The type of data used on this study is secondary data. This study is using Regression Logistic Analisys to testing the hypothesis. The result on this research is there are no influence of Leverage and Profitability to financial distress, and there is negative influence of Liquidity to financial distress. Keyowords : liquidity, leverage, profitabily, financial distress, logistic